2016
DOI: 10.1080/02786826.2016.1256470
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of particles deposited on a single free-fall charged droplet

Abstract: Particles deposited on a free-fall charged droplet were experimentally studied. A droplet, charged under 40% Rayleigh limit, fell through the particle chamber to capture particles by electrostatic attractions. The velocity of the droplet was smaller than 2.1 m/s. The particle-laden droplet eventually spread on a glass slide, which was further analyzed using optical microscope. It was found that the equivalent number of particles captured by the charged droplet were larger than that of uncharged ones by one ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Extensive studies have been reported to elaborate the principle and performance of this technique. 17,19,[23][24][25] Balachandran et al investigated the removal of cigarette smoke, as the source of submicrometer dust, by charged droplets, indicating that the cleaning performance was four times better than that in uncharged cases. 26 Jaworek et al built a multi-nozzle electrospray system and found that the removal efficiency of smoke particles (<1 mm) is up to 80-90% with a very low water consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been reported to elaborate the principle and performance of this technique. 17,19,[23][24][25] Balachandran et al investigated the removal of cigarette smoke, as the source of submicrometer dust, by charged droplets, indicating that the cleaning performance was four times better than that in uncharged cases. 26 Jaworek et al built a multi-nozzle electrospray system and found that the removal efficiency of smoke particles (<1 mm) is up to 80-90% with a very low water consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, without any ionizer, it takes around 24 minutes for the aerosol concentration to reduce by 95%. In the absence of ionizer and ventilation, the removal of human-generated aerosol can be attributed to gravitational settling, which depends on aerosol composition and size [ 39 41 ]. Turning on a commercial ionizer (inset in Figure 3(a) ) reduces the aerosol removal time to 15 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of ionizer and ventilation, the removal of human-generated aerosol can be attributed to two main factors namely evaporation and gravitational settling, both of which depend on aerosol composition and size. [39][40][41] Turning on a commercial ionizer (inset in Figure 3a) reduces the aerosol removal time to 15 minutes. When a small plant-based ionizer was turned on, it shows high efficacy in a 0.5 m 3 enclosure in reducing the time taken to clear the aerosol from 24 minutes to 6 minutes.…”
Section: Number Of Plant-based Ionizersmentioning
confidence: 99%